2022
DOI: 10.3389/fonc.2022.800449
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Preoperative Nomogram for Predicting Benign and Malignant Gallbladder Polypoid Lesions

Abstract: PurposeThe purpose of this study was to develop and validate a preoperative nomogram of differentiating benign and malignant gallbladder polypoid lesions (GPs) combining clinical and radiomics features.MethodsThe clinical and imaging data of 195 GPs patients which were confirmed by pathology from April 2014 to May 2021 were reviewed. All patients were randomly divided into the training and testing cohorts. Radiomics features based on 3 sequences of contrast-enhanced computed tomography were extracted by the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…CT is also often used to examine gallbladder disease because contrast enhancement allows the lesion to be distinguished from the surrounding tissue and aids in the diagnosis of gallbladder disease. The base appearance was found to be an independent predictor of benign and malignant GPs in this analysis, which is consistent with prior studies [ 11 , 12 ]. The size of GPs is one of the most important indications of the nature of the tumor and the need for surgery in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CT is also often used to examine gallbladder disease because contrast enhancement allows the lesion to be distinguished from the surrounding tissue and aids in the diagnosis of gallbladder disease. The base appearance was found to be an independent predictor of benign and malignant GPs in this analysis, which is consistent with prior studies [ 11 , 12 ]. The size of GPs is one of the most important indications of the nature of the tumor and the need for surgery in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
“…To improve the accuracy of the prediction of benign and malignant GPs, several studies have developed multiparametric prediction models that include clinical features, imaging, and radiomics features [ 11 13 ]. Han et al [ 12 ] established a nomogram for predicting benign and malignant polypoid lesions and showed that a model combining clinical features and CT-radiomics (AUC = 0.950) could provide a preoperative prediction of benign and malignant identification. However, feature determination and mapping of regions of interest for feature extraction are highly operator-dependent and unstable performance.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to radiomics models reported in the literature for differentiating between benign and malignant lesions, Han et al (20) showed that their combined model could represent a novel approach to effectively evaluate benign and malignant GPs; however, the AUC of their radiomics model was inferior to that of their clinical model, suggesting that their identified radiomics features were as strong as ours. Comparatively, the model outperformed the clinical model in both the training and test cohorts, thereby confirming the reliability of our proposed model.…”
Section: Discussionmentioning
confidence: 66%
“…The models built by Yuan et al achieved good results in identifying the nature of GBPs [ 19 , 20 ]. Han integrated Radscore, which is calculated by taking 6 radiomics factors into the radiomics model, into the nomogram [ 21 ]. Even though the combined model performed slightly worse than the only clinical model in the testing cohort, it was a promising attempt.…”
Section: Predictive Modelsmentioning
confidence: 99%